RNA Network Interactions During Differentiation of Human Trophoblasts - Chu, Tianjiao; Mouillet, Jean-Francois; Cao, Zhishen; Barak, Oren; Ouyang, Yingshi; Sadovsky, Yoel (Frontiers in Cell and Developmental Biology, 2021)
In the human placenta, two trophoblast cell layers separate the maternal blood from the villous basement membrane and fetal capillary endothelial cells. The inner layer, which is complete early in pregnancy and later becomes discontinuous, comprises the proliferative mononuclear cytotrophoblasts, which fuse together and differentiate to form the outer layer of multinucleated syncytiotrophoblasts. Because the syncytiotrophoblasts are responsible for key maternal-fetal exchange functions, tight regulation of this differentiation process is critical for the proper development and the functional role of the placenta. The molecular mechanisms regulating the fusion and differentiation of trophoblasts during human pregnancy remain poorly understood. To decipher the interactions of noncoding RNAs (ncRNAs) in this process, we exposed cultured primary human trophoblasts to standard in vitro differentiation conditions or to conditions known to hinder this differentiation process, namely exposure to hypoxia (O2 <1%) or to the addition of dimethyl sulfoxide (DMSO, 1.5%) to the culture medium. Using next generation sequencing technology, we analyzed the differential expression of trophoblastic lncRNAs, miRNAs, and mRNAs that are concordantly modulated by both hypoxia and DMSO. Additionally, we developed a model to construct a lncRNA-miRNA-mRNA co-expression network and inferred the functions of lncRNAs and miRNAs via indirect gene ontology analysis. This study improves our knowledge of the interactions between ncRNAs and mRNAs during trophoblast differentiation and identifies key biological processes that may be impaired in common gestational diseases, such as fetal growth restriction or preeclampsia.